Effect of high frequency versus theta‐burst repetitive transcranial magnetic stimulation on suicidality in patients with treatment‐resistant depression. (1st March 2022) - Mehta, Shobha; Downar, Jonathan; Mulsant, Benoit H.; Voineskos, Daphne; Daskalakis, Zafiris J.; Weissman, Cory R.; Vila‐Rodriguez, Fidel; Blumberger, Daniel M.
Abstract: Objective: To investigate the effect of 10 Hz repetitive transcranial magnetic stimulation (rTMS) and intermittent theta‐burst stimulation (iTBS) on suicidality in patients with treatment‐resistant depression (TRD). Methods: We used data from a three‐site randomized clinical trial comparing 10 Hz rTMS and iTBS applied to the left dorsolateral prefrontal cortex (DLPFC) in patients with TRD. We compared the effect of 10Hz rTMS and iTBS on suicidality as measured by the suicide item of the Hamilton Depression Rating Scale 17‐item (HDRS‐17). Results: Suicidality remitted in 71 (43.7%) participants randomized to 10Hz stimulation and 91 (49.1%) participants randomized to iTBS, without a significant difference between the proportions in the two groups ( Χ 2 = 0.674, df = 1, p = 0.4117). There was a significant correlation between change in suicidality and change in depression severity for both modalities (10 Hz, Pearson's r = 0.564; iTBS, Pearson's r = 0.502), with a significantly larger decrease in depression severity for those in whom suicidality remitted compared to those in whom it did not ( t = 10.912, df = 276.8, p < 0.001). Conclusions: Both 10 Hz and iTBS rTMS were effective in reducing suicidality in TRD. Future trials of iTBS for depression should include discrete measures of suicidality.